2019
DOI: 10.1007/s00122-019-03376-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a novel locus involved in non-seed-shattering behaviour of Japonica rice cultivar, Oryzasativa ‘Nipponbare’

Abstract: A novel locus, qCSS3, involved in the non-seed-shattering behaviour of Japonica rice cultivar, 'Nipponbare', was detected by QTL-seq analysis using the segregating population with the fixed known seed-shattering loci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…However, the ILs having mutations at both qSH3 and sh4 slightly inhibited the abscission layer formation, resulting in reduced seed-shattering behaviour (Inoue et al 2015 ; Ishikawa et al 2022 ). In our previous study, we reported qCSS3 , a novel locus involved in reducing seed shattering in the japonica cultivar Nipponbare (Tsujimura et al 2019 ). Studies of these loci suggested that a loss of seed shattering in cultivated rice can be established by the combination of variations at several loci with specific and common mutations among cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ILs having mutations at both qSH3 and sh4 slightly inhibited the abscission layer formation, resulting in reduced seed-shattering behaviour (Inoue et al 2015 ; Ishikawa et al 2022 ). In our previous study, we reported qCSS3 , a novel locus involved in reducing seed shattering in the japonica cultivar Nipponbare (Tsujimura et al 2019 ). Studies of these loci suggested that a loss of seed shattering in cultivated rice can be established by the combination of variations at several loci with specific and common mutations among cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…To identify the rest of the gene(s), an approach that involves fixing the known QTL(s) in the segregating population would be effective for exploring and uncovering the novel QTL(s). Based on this approach, we recently detected QTL for the Control of Seed Shattering in rice on chromosome 3 (qCSS3), a novel locus involved in a loss of seed shattering in japonica rice cultivar O. sativa Nipponbare (Tsujimura et al 2019). Once all the mutations related to a loss of seed shattering are clarified, information on the causal mutations would be very useful to understand the change in the degree of seed shattering conferred by each locus and their additive effects in combination.…”
Section: What Traits Were Targeted For Selection In Early Rice Domestication?mentioning
confidence: 99%
“…Other genes such as SH5 and SSH1/SNB are also believed to have large influences on seed shattering by interacting with qSH1 (Jiang et al 2019a;Yoon et al 2014). Mutagenesis and transgenic methods have been frequently used to illustrate the function and mechanisms of these genes, which affected seed shattering through modifications on AZ formation or lignin deposition in the AZ regions (Jiang et al 2019a;Lv et al 2018;Tsujimura et al 2019).…”
Section: Introductionmentioning
confidence: 99%